The Problems of Using a Google Classroom-based Learning Management System and E-Learning as Online Learning Media in eleven science grader of MAN Tanjungpinang - Septi Riyani; Bony Irawan; Elfa Oprasmani (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2022)
This research aims to examine the problems that exist in the use of the Google Classroom-based Learning Management System and e-learning as an online learning media in eleven science grader of MAN Tanjungpinang. This research is a descriptive quantitative research. The population in this study were eleven science grader of MAN Tanjungpinang. The sampling technique was used total sampling technique where the entire population was sampled so that the number of research sample were 55 students. The research instruments used in this study are a questionnaire instrument to obtain problematic data that occurs in the use of the Google Classroom-based Learning Management System and E-Learning. Based on the results of the study, it was found that the average percentage of problematic use of LMS based on Google Classroom and e-learning at MAN Tanjungpinang was 63.64% which was included in the high problematic category. It can be concluded that there were still many problems faced by students and teachers in online learning that implemented at MAN TanjungpinangKeywords:Problems, Learning Management System, Google Classroom, e-learning